A polyethylenimine-based diazeniumdiolate nitric oxide donor accelerates wound healing. (31st January 2019) - Zhang, Yan; Tang, Keyu; Chen, Bin; Zhou, Su; Li, Nan; Liu, Chuwei; Yang, Jianyong; Lin, Run; Zhang, Tao; He, Weiling
Abstract : A polyethylenimine based diazeniumdiolate nitric oxide donor was prepared to accelerate wound healing. Abstract : Nitric oxide (NO) plays a pivotal role in the cutaneous healing process and a topical supplement of NO is beneficial for wound repair. In this work, a novel polyethylenimine (PEI) based diazeniumdiolate nitric oxide donor was prepared. The obtained polymer (PEI-PO-NONOate) was characterized by Fourier transform infrared (FTIR) spectroscopy, UV-vis absorption spectra, and nuclear magnetic resonance (NMR). The PEI-PO-NONOate polymer was stable under anhydrous conditions at different temperatures. A total of 0.57 μmol gaseous NO was released from 1.0 mg of the PEI-PO-NONOate polymer in PBS of pH 7.4 and it presented a proton-driven release pattern. Furthermore, the PEI-PO-NONOate polymer exhibited a controlled release profile sustained for over 30 hours within the polyethylene glycol (PEG) mixture system. Cytotoxicity evaluation was performed on L929 cells. Full-thickness excisional cutaneous wound models of mice were prepared and the PEI-PO-NONOate polymer was applied to investigate its effects on wound healing. The results revealed that the PEI-PO-NONOates exhibited good biocompatibility. It was also found that the PEI-PO-NONOate polymer promoted cutaneous wound healing and closure with enhanced granulation tissue formation, collagen deposition, and angiogenesis, as compared to the control. In summary, a novel nitric oxide releasing polymer with high loading efficiency and a controlled release profile was developed which presented the potential for application in the acceleration of cutaneous wound healing.